Performance Development of A BLDC Motor Driven Water Pump Using KY Converter - Anu Priya; Sasilatha Sasilatha (Institute of Advanced Engineering and Science, 2018)
This paper presents a performance investigation of bldc motor employing KY converter. Conventional The landsman converter is used to minimize the ripples but the inverter produces high output power ripples, which in turn affect the output of the inverter in The proposed KY converter reduces ripples and smooth dc supply gives to the inverter then it will used to operate brushless dc motor, which inturn improves the motor performance. the electronically commutated brushless DC with voltage source inverter can be operated at fundamental frequency is to reduce switching losses which output in higher efficiency.